2015
DOI: 10.1016/j.pscychresns.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

PBMC telomerase activity, but not leukocyte telomere length, correlates with hippocampal volume in major depression

Abstract: Accelerated cell aging, indexed in peripheral leukocytes by telomere length and in peripheral blood mononuclear cells (PBMCs) by telomerase activity, has been reported in several studies of major depressive disorder (MDD). However, the relevance of these peripheral measures for brain indices that are presumably more directly related to MDD pathophysiology is unknown. In this study, we explored the relationship between PBMC telomerase activity and leukocyte telomere length and magnetic resonance imaging-estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 68 publications
6
33
1
Order By: Relevance
“…Several possible sources of heterogeneity were identified in sampling strategies and analysis methods. Grodstein et al 20 included a sub-group of patients with minimal cognitive impairment, and Wolkowitz et al 21 included a cohort with major depressive disorder. All studies determined relative average telomere length by PCR as the ratio of telomeres to single genes (T/S ratio).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several possible sources of heterogeneity were identified in sampling strategies and analysis methods. Grodstein et al 20 included a sub-group of patients with minimal cognitive impairment, and Wolkowitz et al 21 included a cohort with major depressive disorder. All studies determined relative average telomere length by PCR as the ratio of telomeres to single genes (T/S ratio).…”
Section: Resultsmentioning
confidence: 99%
“…All studies determined relative average telomere length by PCR as the ratio of telomeres to single genes (T/S ratio). Two studies (Grodstein et al 20 and King et al 22 ) used the T/S ratio in statistical analyses, whereas the other three studies (Wikgren et al 12 , Jacobs et al 13 , and Wolkowitz et al 21 ) determined the average telomere base pair length and used that for statistical analyses. One study (King et al 22 ) log-transformed telomere length data prior to analysis in order to better approximate a normal distribution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only one study has assessed the relationship of PBMC basal TA to hippocampal volume in MDD. Wolkowitz et al (In press) reported a significant positive correlation between PBMC basal TA and hippocampal volume in a small group of unmedicated individuals with MDD but not in healthy controls. The authors interpreted these results as being consistent with those of the preclinical study by Zhou et al (2011), reviewed above.…”
Section: Relationship Of Peripheral Cell Aging Markers To the Brainmentioning
confidence: 94%